1992
DOI: 10.1021/ma00038a010
|View full text |Cite
|
Sign up to set email alerts
|

Failure mechanisms of polymer interfaces reinforced with block copolymers

Abstract: The fracture toughness (characterized by the critical energy release rate Gc) of interfaces between polystyrene (PS) and poly(2-vinylpyridine) (PVP) reinforced with poly(styrene-6-2-vinylpyridine) was measured with a double cantilever beam test geometry. The effect of the PVP block degree of polymerization (Wpvp) and the areal density of block copolymer chains at the interface (2) on the measured Gc and on the fracture mechanisms was investigated quantitatively. The PS degree of polymerization (Alps) was kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
492
4
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 462 publications
(520 citation statements)
references
References 12 publications
23
492
4
1
Order By: Relevance
“…A value of 2 nN was used for f b . 7 From eq 10, ⌺ bulk for PS was calculated as 1.32 ϫ 10 18 chains/nm 2 , and for PMMA, it was calculated as 1.77 ϫ 10 18 chains/nm 2 . 13 c was taken as 55 MPa for PS and 80 MPa for PMMA.…”
Section: Chain Friction Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…A value of 2 nN was used for f b . 7 From eq 10, ⌺ bulk for PS was calculated as 1.32 ϫ 10 18 chains/nm 2 , and for PMMA, it was calculated as 1.77 ϫ 10 18 chains/nm 2 . 13 c was taken as 55 MPa for PS and 80 MPa for PMMA.…”
Section: Chain Friction Onlymentioning
confidence: 99%
“…These interfaces would only exhibit high values of G c when the molecular weight of each block exceeded M e . [3][4][5][6][7][8] The low G c values measured for interfaces reinforced with unentangled diblock copolymers suggested that entanglement formation was the primary mechanism of reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…This makes sense in terms of the miscibility of the copolymers in the homopolymers, as these three alternating copolymers are significantly miscible in PMMA (at least up to 10 wt%), thus they are able to expand into and entangle with the homopolymers. Our interpretation of this result is that the increase in molecular weight, increases the effective number of entanglements per chain, N eff ; which has been shown to be directly responsible for the fracture toughness of a biphasic interface [13]. Also supporting this interpretation is an ADCB study by Bernard that showed that the effectiveness of P(S 0.7 -ran-MMA) as an interfacial strengthener increases with M w for four copolymers ranging from 1.60 £ 10 5 to 4.50 £ 10 5 g/mol [22] as well as work by Cho which also observed an increase in G c as a function of M w for compositionally symmetric P(S-ran-MMA) [38].…”
Section: Resultsmentioning
confidence: 85%
“…In this case, the failure occurs by chain scission. Values in the range of 1 to 3 nN have been reported experimentally 9,27,28 as being required to break a C-C bond in a chain scission process. The range of F frict values found in the data in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…We also note that a similar dependence on interfacial chain density was found in the interaction of diblock copolymer brushes at the interfaces in immiscible polymer blends. [9][10][11] When the Σ became sufficiently large, the interfacial strengths were found to level off at a constant value. In Brown's experiments, 13 sliding friction was increased by thin brush layers (i.e.…”
Section: Resultsmentioning
confidence: 99%